Publicizing transgender ballet dancers: a pas de deux of inclusion and reiterative gender norms - Mandradjieff, Mara; Alterowitz, Gretchen (Feminist Media Studies, 2023)
Over the last decade, mainstream media sources from the US and UK have shown an increased interest in topics involving transgender and non-binary populations. Yet, their portrayals of such individuals tend to reaffirm rather than challenge cisnormative ideas surrounding bodies and gender. In this article, we consider this ongoing trend within the highly body-centric, traditionally-gendered artform—classical ballet. With a transgender studies and dance studies lens, we analyze current discourse surrounding the recent move for classical ballet companies and schools to adapt casting and training curricula to better include non-binary dancers. Through these analyses we reveal ways media sensationalizes the transgender body by focusing on information regarding hormone therapy and surgeries, and with the topic of ballet in mind, how this transphobic move becomes intertwined with ballet-specific processes of reshaping the body. We claim that although these popular press pieces contribute to a greater awareness of the lived experiences of transgender and non-binary dancers, they simultaneously reiterate ongoing balletic gender tropes that mark the artform as feminine and designate particular body types and movements to specific binarized genders.
Keywords: Ballet; Bibliographie; Nettoyer; gender; media; non-binary; transgender

Can Rainbow Become the New Pink? A study of ballet educators’ responses to the advancement of LGBTQ+ rights - Hawkes, Tracey (Researching Education Bulletin : Creative Arts Special Edition, 2023)
Keywords: Bibliographie; Nettoyer

Rainbow dancing in Finland and the challenge of transgender inclusion - Kavoura, Anna; Rinne, Santtu (Routledge Handbook of Gender Politics in Sport and Physical Activity, 2022)
Traditionally, partner dances occur between a woman and a man, following rather conservative gender roles and rules. However, as a result of international lesbian, gay, bisexual, transgender, intersex, queer, asexual, allies and more (LGBTIQA+) activism, some social dancing events and competitions have made space for gender and sexual diversity. This chapter focuses on the Rainbow and Same-Sex dancing scene in Finland and its potential and challenges for transgender inclusion. We draw on data collected during the first author’s ethnographic and participatory action research study on trans-inclusive sport spaces and the second author’s experiences as a professional dance teacher and Rainbow trans dancer at both same-sex and mainstream dance competitions. Our findings reveal that the Rainbow dancing movement has helped make dancing more accessible and inclusive for members of the trans community through challenging traditional cis- and heteronormative dance roles and the men-lead/women-follow paradigm. Yet, certain challenges for trans-inclusion persist, such as the transphobic politics and rules of national and international dance associations. In concluding this chapter, we provide recommendations for enhancing access and positive experiences of trans people in dance, DanceSport and sport in general.
Keywords: Bibliographie; Nettoyer

Hypermasculinity Makes the Queer Boy Faint - Alterio, Anthony M. (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Through the lens of personal experience, this chapter provides an exploration of the oft-concealed practices and hypermasculine ideals in dance education. Commercial, concert, and academic dance pedagogy continues to create and perpetuate homophobia that restricts the definition of “boy dancer” to the point of creating a false scarcity and competition to be the most cis-heteronormative male possible. Alterio argues this environment contributes to the perpetuation of discrimination against LGBTQIA+ dancers, the exclusion of non-cis boys, and lack of innovation in the field. Recommendations are offered to those interested in pushing the boundaries of performance and gender identity and a call for institutions to support this work.
Keywords: Bibliographie; Nettoyer

Dancing Boys and Men: Negotiating Masculinity and Sexuality - Christofidou, Andria (Masculinity, Intersectionality and Identity: Why Boys (Don’t) Dance, 2022)
Theatrical dance remains widely perceived as an unconventional activity for boys and young men in many Western contexts. This chapter focuses on professional male dancers’ pathways into recreational, pre-professional dance and assesses the various obstacles encountered and the sources of encouragement available to continue dancing and to pursue a dance career. Data analysis challenges the assumption that homophobia and hierarchies among boys, men, and masculinities have been erased. The chapter argues that wider systems of inequality, oppression, and power persist. These continue to affect boys and young men, influencing their choices and the possibilities to transgress gender norms.

How is the Ballet World Including Non-Binary Dancers? - Lund, Rebekah (Dance Major Journal, 2022)
A few pioneers have shown the way, but who will follow?
Keywords: Bibliographie; Nettoyer

Dancing with Inclusivity: The Importance of Integrating Genderless Terminology into Swing Dance Spaces - Olander, Guinievere.R. (Unbound, 2022)
Keywords: Bibliographie; Nettoyer

A Gap in the Narrative: Exploring the Experiences of Trans Dancers Today - Best, Erica (Collège Ursinus, 2021)
Keywords: Bibliographie; Nettoyer

Super Fluid/Super Black: Translations and Teachings in Transembodied Metaphysics - Whitson, Ni’Ja (Critical Black Futures: Speculative Theories and Explorations, 2021)
Ni’Ja Whitson turns a piece that was originally commissioned as a keynote lecture for the 2020 Collegium for the African Diaspora Dance (CADD) conference, Fluid Black: Dance Back. This chapter is a hybrid text that centralizes Black Transgender and Nonbinary experiences in a conversation of futurity in African Diasporic spirituality, dance traditions, and performativities. Furthermore, Super Fluid/Super Black interrogates beingness through an exploration of astrophysics and global attempts at Black erasure to uncover new strategies of collectivizing under physical, metaphysical, and cosmic bodies that dismantle cisheteronormativity at their core.